2006
DOI: 10.2753/mis0742-1222230202
|View full text |Cite
|
Sign up to set email alerts
|

Information Technology, Production Process Outsourcing, and Manufacturing Plant Performance

Abstract: spans a number of areas, including the productivity effect of information technology, the role of technology in product development, and the economics of software development. He has consulted extensively with Fortune 1000 companies as a Principal with PricewaterhouseCoopers Consulting. His research on information work productivity has been featured in business publications such as Optimize.JONATHAN WHITAKER is a Ph.D. candidate in the Business Information Technology department at the University of Michigan Ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 116 publications
(74 citation statements)
references
References 57 publications
(75 reference statements)
3
68
1
2
Order By: Relevance
“…Recent research has also suggested that products and services with higher information intensity have greater potential to benefit from IT (Andal-Ancion et al 2003, Dehning et al 2003. Studies at the industry (Han et al 2005), firm (Whitaker et al 2005), and plant (Bardhan et al , 2006) levels show that higher IT intensity results in greater use of outsourcing or disaggregation, perhaps because higher IT intensity allows for the separation in time and space of information-intensive activities from physical manipulation activities.…”
Section: H4mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has also suggested that products and services with higher information intensity have greater potential to benefit from IT (Andal-Ancion et al 2003, Dehning et al 2003. Studies at the industry (Han et al 2005), firm (Whitaker et al 2005), and plant (Bardhan et al , 2006) levels show that higher IT intensity results in greater use of outsourcing or disaggregation, perhaps because higher IT intensity allows for the separation in time and space of information-intensive activities from physical manipulation activities.…”
Section: H4mentioning
confidence: 99%
“…Information systems (IS) researchers have used firms (Rai et al 2006, Whitaker et al 2005) and manufacturing plants (Bardhan et al , 2006 to study the role of IT in enabling the unbundling of information and physical flows and the outsourcing of business processes, but they do not explain why information -intensive occupations are more amenable to service disaggregation, and they do not describe the mechanisms that facilitate or inhibit service disaggregation. Because decision making for resource allocation takes place at the occupation level (i.e., firms hire or retrench employees who belong to certain occupations; see Thurm 2007) and because individual employees invest in their human capital to prepare for certain occupations , it is important to understand the role of occupational attributessuch as information intensity, skill level, and the need for physical presence-in service disaggregation to advance theory and inform managerial and individual decision making.…”
Section: Introductionmentioning
confidence: 99%
“…Firms are realizing the importance of developing their outsourcing capabilities and enter into arrangements with vendors to handle both production processes (e.g., fabrication, assembly) and support processes (e.g., logistics, distribution, warehousing, information technology [IT], and product design). Similar to Cisco and Microsoft, many manufacturing plants outsource both production and support processes to achieve the efficiencies derived from the expertise of third-party companies that specialize in these business processes (Bardhan, Whitaker, and Mithas 2006).…”
Section: Introductionmentioning
confidence: 99%
“…We received 152 responses from senior executives (typical designations were President, Senior Vice President, Vice President, Director, and Manager) responsible for purchasing, materials, or procurement. The response rate of 22 percent is similar to or exceeds that of previous empirical studies using survey questionnaires (e.g., Bardhan et al 2007;Bardhan et al 2006;Grover et al 2002). Table 3 shows the characteristics of the respondent firms in terms of firm type (OEM versus component manufacturer), annual sales, and number of employees.…”
Section: Methodsmentioning
confidence: 50%